The heat is on: behavioural, physiological and reproductive evidence of heat stress in breeding king penguins - Aude Noiret; Agnès Lewden; Camille Lemonnier; Céline Bocquet; Marine Montblanc; Fabrice Bertile; Marine Hoareau; Elsa Marçon; Jean-Patrice Robin; Pierre Bize; Vincent A. Viblanc; Antoine Stier (Journal of Thermal Biology, 2026)

Foraging flexibility in response to at-sea constraints in a deep diver, the king penguin: an experimental study - Camille Lemonnier; Charles-André Bost; Nicolas Joly; Antoine Stier; Jean-Patrice Robin; Yves Handrich; Anne Cillard; Marine Montblanc; Pierre Bize; Vincent A. Viblanc (Oecologia, 2025)

Life history stage effects on alert and flight initiation distances in king penguins (Aptenodytes patagonicus) - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2025)

Effects of persistent organic pollutants on telomere dynamics are sex and age-specific in a wild long-lived bird - Roger Colominas-Ciuró; Francesca E. Gray; Kalender Arikan; Sandrine Zahn; Christoph Meier; François Criscuolo; Pierre Bize (Science of The Total Environment, 2024)

Is minimally-invasive sampling the future of persistent organic pollutant (POP) research in birds? A meta-analysis on tissue comparisons - Francesca E. Gray; Davina Derous; Pierre Bize (Chemosphere, 2024)

Surface temperatures are influenced by handling stress independently of corticosterone levels in wild king penguins (Aptenodytes patagonicus) - Agnès Lewden; Chelsea Ward; Aude Noiret; Sandra Avril; Lucie Abolivier; Caroline Gérard; Tracey L. Hammer; Émilie Raymond; Jean-Patrice Robin; Vincent A. Viblanc; Pierre Bize; Antoine Stier (Journal of Thermal Biology, 2024)

Disentangling the “many-eyes”, “dilution effect”, “selfish herd”, and “distracted prey” hypotheses in shaping alert and flight initiation distance in a colonial seabird - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2023)

Foster rather than biological parental telomere length predicts offspring survival and telomere length in king penguins - Vincent A. Viblanc; Quentin Schull; Antoine Stier; Laureline Durand; Emilie Lefol; Jean‐Patrice Robin; Sandrine Zahn; Pierre Bize; François Criscuolo (Molecular Ecology, 2020)
Because telomere length and dynamics relate to individual growth, reproductive investment and survival, telomeres have emerged as possible markers of individual quality. Here, we tested the hypothesis that, in species with parental care, parental telomere length can be a marker of parental quality that predicts offspring phenotype and survival. In king penguins ( Aptenodytes patagonicus ), we experimentally swapped the single egg of 66 breeding pairs just after egg laying to disentangle the contribution of prelaying parental quality (e.g., genetics, investment in the egg) and/or postlaying parental quality (e.g., incubation, postnatal feeding rate) on offspring growth, telomere length and survival. Parental quality was estimated through the joint effects of biological and foster parent telomere length on offspring traits, both soon after hatching (day 10) and at the end of the prewinter growth period (day 105). We expected that offspring traits would be mostly related to the telomere lengths (i.e., quality) of biological parents at day 10 and to the telomere lengths of foster parents at day 105. Results show that chick survival up to 10 days was negatively related to biological fathers’ telomere length, whereas survival up to 105 days was positively related to foster fathers’ telomere lengths. Chick growth was not related to either biological or foster parents’ telomere length. Chick telomere length was positively related to foster mothers’ telomere length at both 10 and 105 days. Overall, our study shows that, in a species with biparental care, parents’ telomere length is foremost a proxy of postlaying parental care quality, supporting the “telomere – parental quality hypothesis.”

Evidence of phenotypic correlation between exploration activity and resting metabolic rate among populations across an elevation gradient in a small rodent species - Mikko Lehto Hürlimann; Julien G. A. Martin; Pierre Bize (Behavioral Ecology and Sociobiology, 2019)

Antioxidant capacity is repeatable across years but does not consistently correlate with a marker of peroxidation in a free-living passerine bird - Charlotte Récapet; Mathilde Arrivé; Blandine Doligez; Pierre Bize (Journal of Comparative Physiology B, 2019)

Senescence in breeding success of female Alpine chamois (Rupicapra rupicapra): the role of female quality and age - Federico Tettamanti; Stefano Grignolio; Flurin Filli; Marco Apollonio; Pierre Bize (Oecologia, 2015)

Senescence in cell oxidative status in two bird species with contrasting life expectancy - Pierre Bize; Sophie Cotting; Godefroy Devevey; Juan van Rooyen; Fabrice Lalubin; Olivier Glaizot; Philippe Christe (Oecologia, 2014)

Pleiotropy in the melanocortin system: expression levels of this system are associated with melanogenesis and pigmentation in the tawny owl ( Strix aluco ) - Guillaume Emaresi; Anne‐Lyse Ducrest; Pierre Bize; Hannes Richter; Celine Simon; Alexandre Roulin (Molecular Ecology, 2013)
The adaptive function of melanin‐based coloration is a long‐standing debate. A recent genetic model suggested that pleiotropy could account for covariations between pigmentation, behaviour, morphology, physiology and life history traits. We explored whether the expression levels of genes belonging to the melanocortin system ( MC 1R , POMC , PC 1/3 , PC 2 and the antagonist ASIP ), which have many pleiotropic effects, are associated with melanogenesis (through variation in the expression of the genes MITF , SLC 7A11, TYR , TYRP 1 ) and in turn melanin‐based coloration. We considered the tawny owl ( Strix aluco ) because individuals vary continuously from light to dark reddish, and thus, colour variation is likely to stem from differences in the levels of gene expression. We measured gene expression in feather bases collected in nestlings at the time of melanin production. As expected, the melanocortin system was associated with the expression of melanogenic genes and pigmentation. Offspring of darker reddish fathers expressed PC 1/3 to lower levels but tended to express PC 2 to higher levels. The convertase enzyme PC 1/3 cleaves the POMC prohormone to obtain ACTH , while the convertase enzyme PC 2 cleaves ACTH to produce α‐melanin‐stimulating hormone (α‐ MSH ). ACTH regulates glucocorticoids, hormones that modulate stress responses, while α‐ MSH induces eumelanogenesis. We therefore conclude that the melanocortin system, through the convertase enzymes PC 1/3 and PC 2, may account for part of the interindividual variation in melanin‐based coloration in nestling tawny owls. Pleiotropy may thus account for the covariation between phenotypic traits involved in social interactions (here pigmentation) and life history, morphology, behaviour and physiology.

Melanin-based colour polymorphism signals aggressive personality in nest and territory defence in the tawny owl (Strix aluco) - Arnaud Da Silva; Valentijn van den Brink; Guillaume Emaresi; Ester Luzio; Pierre Bize; Amélie N. Dreiss; Alexandre Roulin (Behavioral Ecology and Sociobiology, 2013)

Pale and dark reddish melanic tawny owls differentially regulate the level of blood circulating POMC prohormone in relation to environmental conditions - Alexandre Roulin; Guillaume Emaresi; Pierre Bize; Julien Gasparini; Romain Piault; Anne-Lyse Ducrest (Oecologia, 2011)

Indirect Costs of Parasitism are Shaped by Variation in the Type of Immune Challenge and Food Availability - Pierre Bize; Romain Piault; Julien Gasparini; Alexandre Roulin (Evolutionary Biology, 2010)

FECUNDITY AND SURVIVAL IN RELATION TO RESISTANCE TO OXIDATIVE STRESS IN A FREE‐LIVING BIRD - Pierre Bize; Godefroy Devevey; Patricia Monaghan; Blandine Doligez; Philippe Christe (Ecology, 2008)
Major life history traits, such as fecundity and survival, have been consistently demonstrated to covary positively in nature, some individuals having more resources than others to allocate to all aspects of their life history. Yet, little is known about which resources (or state variables) may account for such covariation. Reactive oxygen species (ROS) are natural by‐products of metabolism and, when ROS production exceeds antioxidant defenses, organisms are exposed to oxidative stress that can have deleterious effects on their fecundity and survival. Using a wild, long‐lived bird, the Alpine Swift ( Apus melba ), we examined whether individual red cell resistance to oxidative stress covaried with fecundity and survival. We found that males that survived to the next breeding season tended to be more resistant to oxidative stress, and females with higher resistance to oxidative stress laid larger clutches. Furthermore, the eggs of females with low resistance to oxidative stress were less likely to hatch than those of females with high resistance to oxidative stress. By swapping entire clutches at clutch completion, we then demonstrated that hatching failure was related to the production of low‐quality eggs by females with low resistance to oxidative stress, rather than to inadequate parental care during incubation. Although male and female resistance to oxidative stress covaried with age, the relationships among oxidative stress, survival, and fecundity occurred independently of chronological age. Overall, our study suggests that oxidative stress may play a significant role in shaping fecundity and survival in the wild. It further suggests that the nature of the covariation between resistance to oxidative stress and life history traits is sex specific, high resistance to oxidative stress covarying primarily with fecundity in females and with survival in males.

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Intra-individual variation in body temperature and pectoral muscle size in nestling Alpine swifts Apus melba in response to an episode of inclement weather - Pierre Bize; Aurélie Klopfenstein; Caroline Jeanneret; Alexandre Roulin (Journal of Ornithology, 2007)

Sexual selection in genetic colour-polymorphic species: a review of experimental studies and perspectives - Alexandre Roulin; Pierre Bize (Journal of Ethology, 2007)

Analysis of genetic parentage in the tawny owl (Strix aluco) reveals extra-pair paternity is low - Verena Saladin; Mathias Ritschard; Alexandre Roulin; Pierre Bize; Heinz Richner (Journal of Ornithology, 2007)

Oxygen consumption in offspring tawny owls Strix aluco is associated with colour morph of foster mother - Alexandre Roulin; Pierre Bize; Nathalie Tzaud; Matteo Bianchi; Pierre-Alain Ravussin; Philippe Christe (Journal of Ornithology, 2005)

Covariation between egg size and rearing condition determines offspring quality: an experiment with the alpine swift - Pierre Bize; Alexandre Roulin; Heinz Richner (Oecologia, 2002)